Understanding the nature of Ce-Fe synergy in the structure CaWO4 scheelite for enhanced photocatalytic performance under visible light - Şimsek, Esra Bilgin; Tuna, Ozlem (Elsevier Sci Ltd, 2024)
Doping engineering is a feasible strategy to construct highly efficient photocatalysts. Herein, Ce and Fe mono- and co-doped CaWO4 4 catalysts were synthesized by precipitation method followed by annealing and the degradation activities were tested for the removal of tetracycline antibiotic under visible light irradiation. The experimental results indicated that the photocatalytic activity was greatly improved by co-doping of Ce and Fe elements, in which Fe ions significantly narrowed the band gap energy while Ce dopant increased the oxygen vacancies of CaWO4 4 catalyst. The effects of several experimental conditions (solution pH, initial concentration, co-existing anions, heavy metals, and organic matter) were examined, and the degradation mechanism was explored by radical trapping tests. Furthermore, the photocatalytic efficiency of Ce/Fe-CaWO4 4 catalyst was investigated under natural sunlight irradiation and the degradation performance slightly decreased from 98.4% (simulated sunlight) to 86.8% (natural sunlight) following five repeatability tests, indicating the exceptional stability in outdoor environment. This research demonstrated the synergy of Ce/Fe co-doping and provided novel insights to develop visible-light driven efficient catalysts.
Keywords: CaWO4; Cerium; Iron; Doping; Photocatalysis; Degradation